Influence of Waste Glass Powder as a Supplementary Cementitious Material (SCM) on the Mechanical Properties, Expansion, Environmental Impact, and Microstructure of Cementitious Mortar - Mahdi Bameri; Mohammad Mohammadhasani; Alireza Khaloo; Ashraf Ashour; Morteza NikKhah (Engineering Reports)
ABSTRACT Incorporating waste glass powder (GP) as a partial replacement for Portland cement (PC) in cementitious mortars offers promising environmental and performance benefits. This study evaluates the effects of varying GP content on setting time, flexural and compressive strength, autoclave expansion, environmental impact, and microstructure. The results indicate that increasing GP content prolongs the setting time due to its lower reactivity compared to PC. Although the early strength of GP‐incorporated mortars is substantially lower than that of the control mixture, extended curing durations result in significant strength gains due to ongoing pozzolanic reactions. Autoclave expansion tests show that replacing PC with 30%–40% GP reduces expansion by up to 50%, attributed to the improved particle packing, pozzolanic activity, and optimized pore structure. Environmental impact analysis indicates that both embodied carbon dioxide (ECO2e) and embodied energy (EE) decrease as GP content increases, reflecting its lower environmental footprint compared to PC. Microstructural analysis using scanning electron microscopy (SEM) reveals denser calcium silicate hydrate (C‐S‐H) crystals and refined pore structures in GP 30% and GP 40% mortars. Additionally, energy‐dispersive X‐ray spectroscopy (EDX) analysis shows significant consumption of calcium hydroxide (CH) due to the pozzolanic reaction, suggesting reduced risks of alkali‐silica reaction (ASR) and sulfate attack, thereby enhancing long‐term durability. These findings establish GP as a sustainable supplementary cementitious material (SCM) with significant environmental and performance advantages for future construction applications.